Differences in genetic population structures of Plasmodium falciparum isolates from patients along Thai-Myanmar border with severe or uncomplicated malaria - Pannapa Susomboon (2013)
BACKGROUND: There have been many reports on the population genetic structures of Plasmodium falciparum from different endemic regions, but few studies have examined the characteristics of isolates from patients with different clinical outcomes. The population genetic structures of P. falciparum isolates from patients with either severe or uncomplicated malaria were examined. METHODS: Twelve microsatellite DNA loci from P. falciparum were used to assess the population genetic structures of 50 isolates (i.e., 25 isolates from patients with severe malaria and 25 from patients with uncomplicated malaria) collected in the Thai-Myanmar border area between 2002 and 2005. RESULTS: Genetic diversity and effective population sizes were greater in the uncomplicated malaria group than in the severe malaria group. Evidence of genetic bottlenecks was not observed in either group. Strong linkage disequilibrium was observed in the uncomplicated malaria group. The groups demonstrated significant genetic differentiation (P < 0.05), and allele frequencies for 3 of the 12 microsatellite loci differed significantly between the two groups. CONCLUSION: These findings suggest that the genetic structure of P. falciparum populations in patients with severe malaria differs from that in patients with uncomplicated malaria. The microsatellite loci used in this study were presumably unrelated to antigenic features of the parasites, but, these findings suggest that some loci may influence the clinical outcome of malaria.